Enrichment culture of electroactive microorganisms with high magnetic susceptibility enhances the performance of microbial fuel cells - Chen, Lei; Zhang, Peng; Shang, Weitao; Zhang, Hongxia; Li, Yuntao; Zhang, Weiguo; Zhang, Zhaojie; Liu, Fanghua (Bioelectrochemistry (Amsterdam, Netherlands), 2018)
Many electroactive microorganisms (EAMs) are known as dissimilatory iron-reducing bacteria (DIRB) which can access iron as an electron acceptor to transfer electrons during the process of respiration. Previous research has shown that magnetic susceptibility (χlf) could be used as an indicator of DIRB activities. However, the relationship between χlf and electroactivity of EAMs is still unclear. Here, we report that after sediments of the Sha River enriched with amorphous iron, the χlf of enrichment cultures increased dramatically. The reactor inoculated with higher χlf enrichment cultures started earlier and had a higher peak voltage (0.228 V), higher power density (310.14 mW m−2) and higher coulombic efficiency (10.16%) than lower χlf cultures. Sequencing of bacterial 16S rRNA gene amplicons and χlf measurement revealed that relative abundance of dominant phyla Proteobacteria increased with χlf values in sediments. Further analysis of cyclic voltammetry curves and bacterial terminal-restriction fragment length polymorphism (T-RFLP) of bacterial rRNA genes indicated that the improved performance of the MFCs might be due to a highly electroactive microbial community that the 162 bp terminal restriction fragments (TRFs) originated from. Our results suggested a potential correlation between χlf and presence of EAM indicating a promising route for fast screening in complex environments. •Reactors inoculated with higher χlf cultures show improved MFC performance.•A potential correlation exists between χlf and electroactive microbial communities.•Improved MFC performance is possibly due to EAMs that contain 162 bp TRFs.